Concurrent and longitudinal associations of peers' acceptance with emotion and effortful control in kindergarten. (January 2017) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Diaz, Anjolii; VanSchyndel, Sarah K.; Berger, Rebecca H.; Terrell, Nathan; Silva, Kassondra M.; Spinrad, Tracy L.; Southworth, Jody
The purpose of the study was to evaluate bidirectional associations between peer acceptance and both emotion and effortful control during kindergarten ( N = 301). In both the fall and spring semesters, we obtained peer nominations of acceptance, measures of positive and negative emotion based on naturalistic observations in school (i.e., classroom, lunch/recess), and observers' reports of effortful control (i.e., inhibitory control, attention focusing) and emotions (i.e., positive, negative). In structural equation panel models, peer acceptance in fall predicted higher effortful control in spring. Effortful control in fall did not predict peer acceptance in spring. Negative emotion predicted lower peer acceptance across time for girls but not for boys. Peer acceptance did not predict negative or positive emotion over time. In addition, we tested interactions between positive or negative emotion and effortful control predicting peer acceptance. Positive emotion predicted higher peer acceptance for children low in effortful control.